P223 To be or not to be? – varicella zoster!. (June 2019) - Anwar, Chaudhry Muhammad Asif; Charles, Alwyn; Tierney, Emma; O'Riordan, Aisling; Ramsey, Bart; Murphy, Anne-Marie
Abstract : Background: A rash can create a difficult diagnostic dilemma for the General Paediatrician. Aim/Method: Our aim is to describe the clinical presentation with clinical photos, diagnostic pathway and result of microbiological investigations in a school age child who presented to our Paediatric Emergency department (PED) with an unusual rash ultimately proven to be Varicella Zoster despite vaccination. Results: A previously well 11 years old boy presented to the PED with a rash for four days and a one day history of pyrexia, coryza and cough. The rash started behind the ears and then spread to the entire body including limbs. It was itchy. The family are originally from Quebec and had been residing in Ireland for the past 2 years in relation to the father's occupation. Contact with infectious disease and recent travel were denied. He had never been hospitalised and had no medical diagnoses .His mother was adamant that all vaccinations were up to date and included the Varicella vaccine at one year of age in Canada. He had no known allergies and was not taking any medications. On examination he had multiple vesicular and pustular lesions with an erythematous base. Some lesion had necrotic centres. There were some vesicles on his lower lip, buccal mucosa and also on the throat. His WCC was 2.08, Neutrophils 0.73, Lymphocytes 0.73, CRP 20. Influenza, RSV and Monospot were negative. He was initially treated with IV Augmentin and Flucloxacillin for a presumed diagnosis of Impetigo. More lesions appeared over his trunk and abdomen over the subsequent 24 hours although he was not systemically unwell. The Dermatologist made a clinical diagnosis of 'Chicken Pox'. He was discharged home on an immunocompetent dose of oral acyclovir pending results of skin swab, throat swabs and Varicella titre. At follow up one week later he was clinically well with multiple healing lesions. His Varicella titres were high confirming a diagnosis of Varicella Zoster infection. His mother brought with her his vaccination records from Canada which showed that he had received only one dose of the Varicella vaccine and had missed the booster. This is in contrast to his siblings who were fully vaccinated and did not develop Varicella despite close contact. Conclusion: Common conditions are common. Vaccines can fail. Parents should be encouraged to keep detailed records of all vaccinations including boosters and to follow through with booster vaccines when indicated.